Linguoculture Peculiarities of The English and Uzbek Proverbs with Proper Names (International Journal of Scientific Trends, 2025)
This in the article from the language to the language passing by coming linguocultural features shown. People verbal in his work this genre important role occupies. In the proverb rhyme, impressive content existence for whole world in his words uses. Great English scientists also own in his thoughts proverb how much in our lives important role to play saying past. Not only English scientists, maybe Uzbek poet and writers in his works also obvious indicated illuminated given. Proverbs through foreigners with friendship their connections further is strengthened.